Distribution, ecology and inhibition of Thiobacillus ferrooxidans in relation to acid drainage from Witwatersrand gold mine dumps - Whillier, P. A.(Patricia Ann),1985- (Stellenbosch : Stellenbosch University, 2012)
Thesis (M.Sc.) -- University of Stellenbosch, 1987.